MARTAPURA KOTA INTAN; MARTAPURA DARUSSALAM - nfn Sunarningsih (Balai Arkeologi Kalimantan Selatan, 2007)
Martapura is well known as the city of diamond. This image is far from the real role in the past. Martapura's role as the capital of Banjar Kingdom is over. Nevertheless, some archaeological remain scatter in the town can be seen and they are important and interesting objects to study and probably to revitalise.